Exercise, health and well-being: A philosophical analysis. - Andrew J Bloodworth (2007)
It is commonly thought that exercise improves both our health and well-being. Indeed, prominent psychological researchers argue that exercise which makes us feel good necessarily enhances well-being. Their research employs a subjective conception of well-being, understood in terms of life-satisfaction and affect. Conversely, I argue that pleasure, enjoyment and desire-fulfilment do not necessarily enhance well-being. Subjective judgements of well-being can be mistaken. Exercise is of merely instrumental value in preserving functionings and capabilities that constitute well-being. This understanding of well-being draws extensively upon Nussbaum's capabilities approach. The biomedical case for the health benefits of exercise excludes subjective valuing, presupposing a dichotomy between objective scientific fact and subjective value. Health is understood in naturalistic terms, focusing upon the absence of disease and illness. In contrast, I argue health cannot be isolated from those functionings and capabilities constitutive of well-being which entangle fact and value. To be healthy is to be in a bodily and mental state that ensures the capability to function in valuable ways. Rejecting the fact/value dichotomy paves the way for reflection upon those values central to well-being. I argue for an objective list theory of well-being, in which listed constituents, such as affiliation and play, are considered valuable independent of possibly flawed subjective valuations. The human body, however, is not merely a vessel for listed values. Griffin elevates our rational nature over our animality in proposing his theory of well-being. His theory appears distant from some of our most central concerns as embodied human beings. Ageing, disease and illness mark some of the ways in which our bodies limit our capabilities. The capabilities and functionings proposed in Nussbaum's approach reflect both our animal and rational nature. In conclusion, I argue that exercise offers one important way in which to preserve the physical preconditions of these valuable functionings and capabilities.